Resilience in elderly people: factors associated with sociodemographic and health conditions - Fernanda Resende Rodrigues; Darlene Mara dos Santos Tavares (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe the sociodemographic and health characteristics of elderly people, measure the score of total resilience and by sex and verify the association of sociodemographic and health variables with total resilience and by sex. Methods: this is a household survey with 808 elderly people, assessed by validated instruments. Student's t test and multiple linear regression (p<0.05). Results: most were female, 60|-|79 years old. The total resilience score was 78.06, for men 81.53 and for women, 76.32. Total resilience was associated with males; positive self-perceived health; greater participation in Advanced Activities of Daily Living; fewer morbidities; absence of depressive symptoms. Among men and women, resilience was associated with greater participation in Advanced Activities of Daily Living and absence of depressive symptoms and, specifically, among women, positive self-perceived health. Conclusion: these results contribute to nursing care, aiming to encourage resilience.